Altered Interatrial Conduction Detected in MADIT II Patients Bound to Develop Atrial Fibrillation - Holmqvist, Fredrik (Ann Noninvasive Electrocardiol, 2009)
Background: Changes in P‐wave morphology have recently been shown to be associated with interatrial conduction route used, without noticeable changes of P‐wave duration. This study aimed at exploring the association between P‐wave morphology and future atrial fibrillation (AF) development in the Multicenter Automatic Defibrillator Trial II (MADIT II) population. Methods: Patients included in MADIT‐II without a history of AF with sinus rhythm at baseline who developed AF during the study (“Pre‐AF”) were compared to matched controls without AF development (“No‐AF”). Patients were followed for a mean of 20 months. A 10‐minute high‐resolution bipolar ECG recording was obtained at baseline. Signal‐averaged P waves were analyzed to determine orthogonal P‐wave morphology, P‐wave duration, and RMS20. The P‐wave morphology was subsequently classified into one of three predefined types using an automated algorithm. Results: Thirty patients (age 68 ± 7 years) who developed AF during MADIT‐II were compared with 60 patients (age 68 ± 8 years) who did not. P‐wave duration and RMS20 in the Pre‐AF group was not significantly different from the No‐AF group (143 ± 21 vs 139 ± 30 ms, P = 0.26, and 2.0 ± 1.3 vs 2.1 ± 1.0 μV, P = 0.90). The distribution of P‐wave morphologies was shifted away from Type 1 in the Pre‐AF group when compared to the No‐AF group (Type 1/2/3/atypical; 25/60/0/15% vs 10/63/10/17%, P = 0.04). Conclusions: This study is the first to describe changes in P‐wave morphology in patients prior to AF development. The results indicate that abnormal interatrial conduction may play a role in AF development in patients with prior myocardial infarction and congestive heart failure.